Comparative study on the enhancement of spray cooling heat transfer using conventional and bio-surfactants - Liu, Pengfei (2022)
In this paper, a comparative study is performed to evaluate the enhancement of spray cooling heat transfer using deionized water with a conventional surfactant (Tween 20) and two biosurfactants (Rhamnolipid and Sophorolipid). In the single-phase regime, appreciable enhancement on spray cooling heat transfer can be achieved using Rhamnolipid additive. However, the addition of Sophorolipid leads to a decrease in the single-phase spray cooling heat transfer. Meanwhile, in the nucleate boiling, spray cooling heat transfer is substantially enhanced using any of the three tested surfactants due to the decrease in surface tension and enhanced wettability. At the same concentration, the two biosurfactants lead to higher heat transfer than Tween 20 due to their lower surface tension as compared to Tween 20. The maximum spray cooling heat transfer enhancement is found to be 37%, 55%, or 41% using Tween 20, Rhamnolipid, or Sophorolipid, respectively as compared to deionized water. The surface condition after testing is also studied. Residual deposition is observed after testing when Rhamnolipid is added into deionized water whereas the addition of Sophorolipid leads to strong surface oxidation after testing. The strong surface oxidation causes the decrease in the rate of increment of the heat flux with increasing temperature difference. Comparatively, no distinction can be observed before and after testing when Tween 20 solution is used.